Electroplating Composition for High-Hardness Silver-Antimony Binary Alloy Coating
The electroplating composition stabilizes silver-antimony alloy plating by using potassium antimony tartrate and Rochelle salt to enhance hardness and gloss, while stearoxytrimethylsilane reduces brittleness and simethicone prevents bubble formation, addressing stability and surface quality issues in Ag-Sb plating.
Patent Information
- Application Number
- KR1020250205080
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-12-19
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2045-12-19
AI Technical Summary
Silver-antimony (Ag-Sb) alloy plating suffers from low chemical stability, leading to precipitation of metal ions, reduced hardness, and deterioration of gloss due to pH and temperature fluctuations, resulting in unstable plating baths and surface quality issues.
An electroplating composition comprising silver ion source, antimony ion source, tartrate, selenium compound, polyphosphate, and potassium nitrate, with potassium antimony tartrate and Rochelle salt stabilizing antimony ions, stearoxytrimethylsilane reducing brittleness, and simethicone preventing bubble formation, to enhance hardness, gloss, and conductivity.
The composition achieves high hardness (200 Hv or higher), improved wear resistance, and enhanced glossiness by controlling precipitation and brittleness, ensuring stable and uniform plating layers.
Smart Images

Figure 112025144417608-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to an electroplating composition that forms a silver-antimony binary alloy plating layer capable of exhibiting high hardness, which can be applied to sockets, which are interface components for charging electric vehicles, connectors of electrical and electronic communication components, lead frames, and printed circuit boards. Background Technology
[0003] Silver (Ag) is widely used as a surface plating layer in a wide range of electrical and electronic component fields due to its excellent electrical conductivity, reflectivity, and corrosion resistance. However, silver has the disadvantage of having relatively low hardness and poor wear resistance, and it wears out quickly or gets scratched in environments such as electrical contacts or connectors where repetitive physical contact occurs. To solve these problems, a technology has been proposed to improve the mechanical properties of the plating layer by adding trace amounts of alloying elements to silver.
[0004] Among them, silver-antimony (Ag-Sb) alloy plating is known as a representative approach to compensate for the disadvantages of silver.
[0005] However, silver-antimony (Ag-Sb) alloy plating is Sb 3 + Due to the low chemical stability of the ions, they easily precipitate in the form of base salts or hydroxides with changes in pH or temperature fluctuations, which leads to problems such as reduced hardness and gloss.
[0006] In other words, silver-antimony (Ag-Sb) alloy plating can actually result in lower hardness due to the precipitation of metal ions and the lack of long-term stability of the plating bath, and there is a problem in that the gloss can also be reduced due to the deterioration of the brightener function and unstable surface quality caused by these precipitates. Prior art literature
[0008] Republic of Korea Patent Registration No. 10-953228 The problem to be solved
[0009] The present invention was devised to solve the problems described above and aims to provide an electroplating composition that forms a silver-antimony binary alloy plating layer capable of exhibiting high hardness. means of solving the problem
[0011] As a means to solve the aforementioned problems, the silver-antimony binary alloy electroplating composition of the present invention (hereinafter referred to as the "composition of the present invention") comprises, for every 100 parts by weight of water, 0.1 to 10 parts by weight of a silver ion source, 0.001 to 5 parts by weight of an antimony ion source, 5 to 100 parts by weight of a tartrate, 0.0001 to 0.1 parts by weight of a selenium compound, 0.05 to 2 parts by weight of a polyphosphate, and 3 to 20 parts by weight of potassium nitrate, wherein the addition of the polyphosphate suppresses the formation of antimony ion precipitation, and the addition of the potassium nitrate compensates for the decrease in conductivity of the plating bath caused by the addition of the polyphosphate.
[0012] As one example, the above antimony ion source is characterized as being potassium antimony tartrate.
[0013] As one example, the above tartrate is characterized as being a Rochelle salt.
[0014] As an example, it is characterized by further including 0.001 to 0.02 parts by weight of stearoxytrimethylsilane.
[0015] delete
[0016] delete
[0017] As an example, it is characterized by further including 0.001 to 0.01 parts by weight of simethicone. Effects of the invention
[0019] As explained above, the composition of the present invention has the advantage of exhibiting high hardness (200 Hv or higher) by controlling the formation of insoluble precipitates.
[0020] In addition, the composition of the present invention has the advantage of being able to improve glossiness by controlling the formation of insoluble precipitates, etc.
[0021] In addition, the composition of the present invention has the advantage of improving wear resistance by enhancing resistance to brittleness. Brief explanation of the drawing
[0023] Figures 1 and 2 are drawings showing the results of a hardness analysis experiment. Specific details for implementing the invention
[0024] Hereinafter, the structure and operation of the present invention will be explained in more detail with reference to the attached drawings. In describing the present invention, terms and words used in this specification and claims must be interpreted in a meaning and concept consistent with the technical spirit of the present invention, based on the principle that the inventor can appropriately define the concept of the terms to describe his invention in the best way possible.
[0026] The composition of the present invention is characterized by comprising, per 100 parts by weight of water, 0.1 to 10 parts by weight of a silver ion source, 0.001 to 5 parts by weight of an antimony ion source, 5 to 100 parts by weight of a tartrate, and 0.0001 to 0.1 parts by weight of a selenium compound.
[0027] The above silver ion source (Ag + As a main metal source for forming a plating layer, silver cyanide (AgCN), silver nitrate (AgNO3), silver sulfate, silver amino complex, etc., which have excellent solubility and dissociability, can be applied.
[0028] Among these, silver cyanide or silver nitrate has the advantage of high solubility in aqueous solution, excellent dissociability of silver ions, and forming stable complexes with Rochelle salt and tartrate salts described below, which can uniformly supply silver ions during the plating process.
[0029] The above antimony ion source (Sb 3+) is an alloy component that induces improvement in hardness and grain refinement of the plating layer. Antimony compounds such as potassium antimony tartrate, antimony chloride, antimony nitrate, and antimony oxide can be used as the antimony ion source.
[0030] However, common antimony compounds have a problem in that they react sensitively to changes in pH or temperature in aqueous solutions, making them prone to forming precipitates in the form of antimony hydroxide or base salts.
[0031] In particular, antimony chloride, antimony nitrate, and antimony oxide have low dissociation stability in the plating bath and can adversely affect the density and uniformity of the plating layer by causing fine sludge formation and solution turbidity during long-term operation.
[0032] On the other hand, potassium antimony tartrate has the characteristic that tartaric acid-based ligands complex the antimony ion and maintain it in a stable complex ion state.
[0033] Accordingly, potassium antimony tartrate has the advantage of significantly lowering the likelihood of precipitation in the solution and maintaining a relatively stable ionic state even under pH changes or long-term operating conditions of the plating bath, thereby improving the long-term stability of the plating bath.
[0034] Therefore, in the present invention, it is preferable to use potassium antimony tartrate, which has the best solution stability, as an antimony ion source, thereby minimizing the occurrence of precipitates in the plating bath and stably securing the uniformity, gloss, and hardness characteristics of the silver-antimony alloy plating layer.
[0035] The above tartrate forms a stable complex in solution through a complexation reaction with silver and antimony ions, thereby controlling the precipitation of metal ions and the formation of base salts. Potassium sodium tartrate (Rochelle salt), potassium tartrate, sodium tartrate, etc. may be used as the above tartrate.
[0036] In particular, sodium potassium tartrate (Rochelle salt) is the most desirable among the above tartrate salts because it has excellent solubility, buffering capacity, and complexing ability, thereby most effectively achieving the stabilization of metal ions in the electroplating bath.
[0037] Silver and antimony ions tend to precipitate in aqueous solutions in the form of hydroxides or base salts, but Rochelle salt forms appropriate complexes with these metal ions to inhibit precipitation and stabilize the plating bath. In addition, Rochelle salt contributes to the crystallization of the plating layer by gently controlling the supply rate of silver ions during plating, and also performs the function of assisting the action of the brightener.
[0038] The above selenium-based compound acts as a brightener, refining silver crystal grains and improving surface leveling through surface-selective adsorption. It exhibits a powerful gloss / smoothing effect even in minute amounts.
[0039] Meanwhile, silver-antimony plating has the advantage of very high hardness, but consequently, the brittleness of the plating layer increases, which may lead to microcracks and delamination during bending deformation.
[0040] Accordingly, the present invention provides an example in which, in addition to the above compositions, 0.001 to 0.02 parts by weight of stearoxytrimethylsilane are further included.
[0041] The above-mentioned stearoxytrimethylsilane is an organic additive having a long stearyl chain and a silane structure, which selectively adsorbs to the intergranular region of silver crystals during the plating process to relieve local stress and reduce the brittleness of the plating layer.
[0042] These stearoxytrimethylsilanes alleviate brittleness problems, improving bending durability while maintaining the hardness of the plating layer (200 Hv or higher).
[0043] Meanwhile, as previously mentioned, Rochelle salt is added to the composition of the present invention to control the formation of precipitates. However, in order to further increase the efficiency of controlling the formation of such precipitates and to double the hardness and glossiness, the present invention provides an example in which, in addition to the above compositions, 0.05 to 2 parts by weight of polyphosphate are further included per 100 parts by weight of water.
[0044] Sb 3 + It is sensitive to changes in pH and precipitation occurs easily, but polyphosphates form weak complexes with these metal ions to increase stability in solution.
[0045] The above polyphosphate may include sodium pyrophosphate, sodium triphosphate, sodium hexametaphosphate, sodium polyphosphate, etc.
[0046] On the other hand, while the addition of only polyphosphate is advantageous for stabilizing metal ions, it can act as a factor that reduces the conductivity of the plating solution and lowers gloss. If the conductivity of the plating bath decreases, the migration speed of metal ions slows down, leading to irregular electrodeposition rates and grain coarsening, which causes a decrease in hardness. Furthermore, since reduced conductivity inhibits the selective adsorption of brighteners and weakens the surface leveling effect, it can cause a decrease in the gloss of the plating layer.
[0047] Accordingly, the present invention provides an example in which 3 to 20 parts by weight of potassium nitrate are further included in addition to the polyphosphate.
[0048] The above potassium nitrate has the function of increasing the conductivity of the plating bath and improving the electrodeposition rate without strongly complexing with metal ions. Due to this, the hardness and gloss of the plating layer can be doubled.
[0049] On the other hand, when potassium nitrate is added, the increase in conductivity and the influence of gas generation reactions can lead to an increase in bubbles in the plating bath, which can cause pinholes and pitting on the surface of the plating layer and result in a decrease in gloss.
[0050] Accordingly, the present invention provides an example in which 0.001 to 0.01 parts by weight of simethicone are further included in addition to the above composition.
[0051] The above simethicone is a siloxane-based defoaming agent that suppresses the generation of bubbles and adhesion to the plated surface during plating, thereby minimizing surface defects that may occur during the formation of the plating layer and enabling the expression of effects that improve gloss and surface uniformity.
[0053] Embodiments of the present invention are explained below through experimental examples.
[0054] As shown below, after preparing each plating solution, a degreasing and activated brass plate (thickness 0.5 mm, 20 mm × 50 mm) was used as the cathode, the temperature was 25℃, and the current density was 1.0 A / dm². 2 , plating was performed under conditions of a plating time of 10 minutes to form a plating layer approximately 10 μm thick. After plating, the specimens were washed with pure water and dried at 60°C for 10 minutes, after which the following brittleness evaluation, hardness measurement, and gloss measurement tests were performed, and the results are shown in Table 1.
[0055] First, for the brittleness evaluation, each plated specimen was cut to a width of 10 mm to prepare a test specimen. Then, using a mandrel with a diameter of 5 mm, a 180° bend was defined as one cycle with the plating layer facing outward, and repeated bending was performed. After each bend, the outer side of the bent portion was observed under an optical microscope (magnification 200x), and the point at which a noticeable crack or delamination was first observed in the plating layer was recorded as the "number of times the first crack occurred."
[0056] Next, a micro Vickers hardness tester was used for hardness measurement. The test load was set to 25 gf (0.245 N) and the holding time was set to 10 seconds. For each specimen, hardness values were measured at five different points, and the average value was taken as the hardness value.
[0057] Next, gloss was measured using a gloss meter under a 60° angle of incidence condition. Gloss was measured at five points relative to the center of the plated surface of each specimen, and the average value was taken as the gloss. The unit used was 60° Gloss Unit (GU).
[0059] <Example 1>
[0060] A plating solution was prepared to contain 2 parts by weight of a silver ion source (silver nitrate), 0.05 parts by weight of an antimony ion source (potassium antimony tartrate), 20 parts by weight of Rochelle salt, and 0.005 parts by weight of a selenium compound (selenate) per 100 parts by weight of water.
[0062] <Example 2>
[0063] A plating solution was prepared in the same manner as in Example 1, but with an additional 0.001 parts by weight of stearoxytrimethylsilane.
[0065] <Example 3>
[0066] A plating solution was prepared in the same manner as in Example 1, but with an additional 0.1 weight part of polyphosphate (sodium pyrophosphate).
[0068] <Example 4>
[0069] A plating solution was prepared in the same manner as in Example 3, but with an additional 5 parts by weight of potassium nitrate.
[0071] <Example 5>
[0072] A plating solution was prepared in the same manner as in Example 4, but with an additional 0.005 parts by weight of simethicone.
[0074] division Number of bends at which the first crack occurs (times) Vickers hardness Hv(average, n=5) 60° Glossiness (GU, average, n=5) Example 1 3 207 82 Example 2 10 205 83 Example 3 5 210 85 Example 4 5 214 87 Example 5 7 213 90
[0076] When comparing Example 1 and Example 2 in terms of brittleness, in the case of Example 2, the number of bending cycles at which the first crack occurs was significantly increased compared to Example 1 due to the addition of more stearoxytrimethylsilane, confirming the effect of mitigating the brittleness of the plating layer.
[0077] In addition, in Examples 4 and 5, it can be seen that the bending durability is somewhat improved compared to Example 1 due to the addition of polyphosphate and potassium nitrate, and in particular, in the case of Example 5 which further includes simethicone, it can be seen that cracks occur at a higher number of bending cycles than in Examples 3 and 4, which is attributed to the reduction of local brittle defects caused by bubbles.
[0078] Next, we examine the hardness and gloss. In terms of hardness, it was confirmed that in all embodiments, a high-hardness plating layer was formed with a Vickers hardness of 200 Hv or higher.
[0079] In Example 3, it can be seen that the density of the plating layer is improved by suppressing the formation of precipitates in the plating bath through the addition of polyphosphate, and as a result, compared to Example 1, the hardness increased from 205 Hv to 208 Hv and the glossiness increased from 82 GU to 85 GU.
[0080] In addition, in Example 4, potassium nitrate was added in addition to the polyphosphate to compensate for the conductivity that could be reduced by the polyphosphate, thereby improving the electrodeposition efficiency. As a result, the hardness was further increased to 212 Hv, and the gloss was also improved to 87 GU.
[0081] In addition, in Example 5, simethicone was further included to suppress bubble formation that may increase incidentally due to the addition of potassium nitrate, and as a result, pinhole and pitting defects on the surface of the plating layer were reduced, resulting in the highest gloss value of 90GU.
[0082] Meanwhile, as it can be seen that in Example 2, in which stearoxytrimethylsilane was added, substantially equivalent hardness and glossiness were maintained compared to Example 1, it can be seen that brittleness can be mitigated without a decrease in hardness and glossiness by adding stearoxytrimethylsilane.
[0084] From the above description, those skilled in the art will understand that various changes and modifications are possible within the scope of the technical concept of the present invention. Accordingly, the technical scope of the present invention should not be limited to the contents described in the detailed description of the specification, but should be determined by the claims.
Claims
Claim 1 A silver-antimony binary alloy electroplating composition comprising, per 100 parts by weight of water, 0.1 to 10 parts by weight of a silver ion source, 0.001 to 5 parts by weight of an antimony ion source, 5 to 100 parts by weight of a tartrate, 0.0001 to 0.1 parts by weight of a selenium compound, 0.05 to 2 parts by weight of a polyphosphate, and 3 to 20 parts by weight of potassium nitrate, wherein the addition of the polyphosphate inhibits the formation of antimony ion precipitation, and the addition of the potassium nitrate compensates for the decrease in conductivity of the plating bath caused by the addition of the polyphosphate. Claim 2 A silver-antimony binary alloy electroplating composition according to claim 1, characterized in that the antimony ion source is potassium antimony tartrate. Claim 3 A silver-antimony binary alloy electroplating composition according to claim 1, characterized in that the tartrate is a Rochelle salt. Claim 4 A silver-antimony binary alloy electroplating composition according to claim 1, further comprising 0.001 to 0.02 parts by weight of stearoxytrimethylsilane. Claim 5 delete Claim 6 delete Claim 7 A silver-antimony binary alloy electroplating composition characterized by further including 0.001 to 0.01 parts by weight of simethicone in claim 1.
Citation Information
Patent Citations
Sedimentation improving agent for material to be plated, and barrel plating method using the sedimentation promoting agent
JP2008266714A
Cyanide-free electrolyte for silver deposition
JP2021535276A
Method for manufacturing color steel sheets
KR1020130026150A
Low temperature bonding method using metal coating layer with exothermic and amorphous characteristics
KR1020170014720A
Articles including surface coatings and methods to produce them
US20250326936A1
